A Critical Analysis of the Book Ma’āni al-Abniah fi al-Arabiah (Meanings of Structures in Arabic) - Hassan Sarbaz; Azad Mounesi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Ma’āni al-Abniah fi al-Arabiah (‘Meanings of Structures in Arabic’) is a valuable work by Fādil Sālih Sāmarrā’i, where he explains the meanings of structures and different conjugates proceeding with his innovative project involving a semantic approach to morphology and syntax. He argues that any change in a structure or conjugate leads to a change in its meaning, and consideration of the diversity of these meanings increases the importance of Arabic and the rhetoric contained in the Holy Quran. In this book, Sāmarrā’i has adopted a semantic approach to investigate the issues concerning nouns and verbs, infinitives, adverbs of time and place, present participles, past participles, constant adjectives, instruments, different types of plural, and relative nouns. With a descriptive content-analytical method, this research attempts first to address the role of Fādil Sālih Sāmarrā’i in the innovation of morphology and his emphasis on the relationship between morphological structures and their meanings and then to scientifically analyze his success in that regard and the most significant advantages and imperfections of Ma’āni al-Abniah fi al-Arabiah with a critical review of the book.